Tren Penelitian Etnosains dalam Pembelajaran IPA: Tinjauan Literatur Global dan Lokal - I Nyoman Maha Budhi Sujana; I Nyoman Suardana; Ni Made Pujani (CV. ITTC INDONESIA, 2026)
Contemporary science education faces the challenge of a gap between abstract theoretical concepts and students' sociocultural realities, which impacts the generally low achievement of science literacy. The ethnoscience approach emerges as a paradigmatic offering to bridge modern science with local community knowledge systems. However, the implementation trends and comparisons of its effectiveness at both global and national scales have not been systematically mapped. This study aims to analyze research trends in ethnoscience within science learning through a review of global and local literature in order to identify cultural integration patterns and compare learning models. The method used is a systematic literature review with purposive sampling technique. The research sample consisted of 14 scientific articles, comprising 5 reputable international articles and 9 accredited national articles published in the period 2021–2026. Data analysis was carried out through stages of identification, information extraction, categorization, and critical synthesis to uncover gaps and compare international and national research patterns. The findings indicate that global trends explore ethnoscience from diverse cultural contexts with a primary focus on sustainable education and the decolonization of the science curriculum. Meanwhile, local Indonesian trends place greater emphasis on the utilization of Nusantara (archipelagic) wisdom in primary and secondary science learning. Both perspectives consistently demonstrate that ethnoscience-based learning is effective in improving science literacy, sharpening critical thinking, and preserving local culture. The essential difference lies in their orientation: global research focuses on philosophical and macro-policy domains, whereas national research is highly applicative, with a dominance of PBL and PjBL models. Identified gaps include a scarcity of longitudinal studies, limited exploration of pure physics through an ethnoscience lens, and the suboptimal use of digital technology for the preservation of traditional knowledge.